COVID-19: Beyond washing your hands and social distancing - DeBeliso, M.; Berning, J. M.; Carson, C.; Sevene, T.; Harris, C.; Adams, K. J.; Walsh, J.; Climstein, M. (International Journal of Science and Engineering Investigations, 2020)
A pandemic due to the outbreak of the COVID-19 virus was declared as of March 2020. The authors provide perspective towards preventing and/or mitigating the impact of contracting the virus known as COVID-19. The authors posit straightforward strategies that an individual could implement that may decrease the likelihood of developing COVID-19, help lessenthe severity of the symptoms relatedtothe COVID-19and potentially mitigate the transmission of the virus.The authors consider their comments as food for thought and not as professional medical advice. If you believe you have contracted the COVID-19 virus seek the advice of your healthcare provider.